'Now I can never go back': The thwarted returns of temporary labour migrants from China in Perth, Western Australia. Issue 1 (1st March 2017) - Stevens, Catriona
From the early 2000s onwards, labour migrants from China with technical work skills but low educational attainment arrived in Australia with fixed-term, temporary plans. Yet, to their surprise, many have been thwarted in their plans to return, and have instead experienced an unexpected transition to permanent residency (PR). Reasons include rapid economic growth in China and the rising cost of housing; the challenges of re-entering the competitive Chinese education system for children accustomed to Australian schools; and the realization that time spent overseas has limited work opportunities upon return. They describe their experiences in terms that closely resemble classical labour migrations of colonial and postcolonial eras. Return and discourses of return must be understood within contemporary migration models that emphasize circular, transient and open-ended mobility. Yet individual migrants still articulate migration trajectories and return plans that are grounded in simpler conceptions of 'here' and 'there'. While recognizing the contemporary shift towards mobile and transnational lives among elites and non-elites alike, it is important not to overlook the very real and material barriers to return that some temporary migrants claim to experience.